Assessment of angular distortion of structures adjacent to a road embankment site. (October 2015) - Kim, Tae-Hyung; Kim, Kook-Han; Choi, Young-Chul
Highlights: Angular distortion caused by differential settlement of soil is a critical factor. We discussed the limitations of current measurement systems used in the field. An alternative method was proposed and demonstrated in road construction site. The new method better represented the angular distortion of the structure. Abstract: Angular distortion caused by differential settlement critically influences the damage to and serviceability of a structure. The angular distortion criterion proposed by Bjerrum generally is used in practice. However, some measurements used in the field do not properly represent the angular distortion of a structure in a way that allows Bjerrum's criterion to be applied. This paper includes a discussion of using the measured data obtained from ground and structures near road embankment sites over deep soft soil. The data analysis revealed several problems, such as an insufficient number of measurement gauges, improper installation of gauges, and incorrect understanding of the angular distortion during data interpretation. An improved measurement method, called "relative displacement measurement, " was suggested. The proposed method was demonstrated in the field. Compared to the previous measurement, this method provides more accurate measurement of the relative displacement between columns of the structure and better represents the angular distortion.